MODUL AJAR/RANCANGAN PELAKSANAAN PEMBELAJARAN MODEL PEMBELAJARAN INOVATIF DAN INTERAKTIF (PENERAPAN PEMBELAJARAN PROBLEM BLESED LEARNING) - RASMAITA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to describe the Pancasila Education learning process for sixth-grade elementary school students using conventional learning (Based Learning). This qualitative research was conducted at SDN 1 Mesuji Timur during the odd semester of the 2025 academic year. The primary data obtained by the researcher were sixth-grade teachers at SDN Mesuji Timur, who observed the conventional learning (Based Learning) in Pancasila Education lessons. This teaching module/Lesson Implementation Plan (RPP) describes an innovative and interactive learning model designed to transform conventional learning patterns into more active and engaging ones for students. This innovative learning focuses on active student engagement, utilizing models such as problem-based learning (PBL) or project-based learning (PBL), which encourage students to directly engage in the learning process. The goal is to develop students' critical thinking skills, problem-solving abilities, and intellectual abilities, as well as to create a dynamic learning environment where students become active participants, not just passive recipients of information. Through the implementation of this model, it is hoped that more effective and meaningful learning objectives can be achieved.